2020
DOI: 10.1021/acs.jmedchem.0c00016
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Grafting of Cancer Cells with Antigenic Epitopes Promotes Selective Antibody-Mediated Cytotoxicity

Abstract: A growing class of immunotherapeutic agents work by redirecting components of the immune system to recognize specific markers on the surface of cancer cells and initiate a selective immune response. However, such immunotherapeutic modalities will remain confined to a relatively small subgroup of patients until two major hurdles are overcome: (1) the specific targeting of cancer cells relative to healthy cells, and (2) the lack of common targetable tumor biomarkers among all patients. Here, we designed a unique… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 69 publications
2
18
0
Order By: Relevance
“…14,15 Antibodyrecruiting molecules (ARMs) are bifunctional molecules composed of cell-targeting moiety and antibody-binding component, which could bridge the target cells and immune system and induce downstream immunity to eliminate the target cells. 16,17 Many rationally designed ARMs, where preferred haptens that could be recognized by natural occurring endogenous antibodies, such as dinitrophenyl (DNP), galactose-α-1,3-galactose (αGal) and rhamnose (Rha), as an antibody-binding component, have been successfully achieved in cancer, [18][19][20][21][22] virus, 23, 24 bacterial 25,26 and others. 27 For example, we and others demonstrated that nanobody-DNP conjugates could form an in situ immune-complex with specific endogenous anti-DNP antibody existing in human serum and subsequently provoke potent ADCC and CDC cytotoxicity to target destructing cancer cells in vitro and exhibit in vivo antitumor activity in mouse xenograft models.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Antibodyrecruiting molecules (ARMs) are bifunctional molecules composed of cell-targeting moiety and antibody-binding component, which could bridge the target cells and immune system and induce downstream immunity to eliminate the target cells. 16,17 Many rationally designed ARMs, where preferred haptens that could be recognized by natural occurring endogenous antibodies, such as dinitrophenyl (DNP), galactose-α-1,3-galactose (αGal) and rhamnose (Rha), as an antibody-binding component, have been successfully achieved in cancer, [18][19][20][21][22] virus, 23, 24 bacterial 25,26 and others. 27 For example, we and others demonstrated that nanobody-DNP conjugates could form an in situ immune-complex with specific endogenous anti-DNP antibody existing in human serum and subsequently provoke potent ADCC and CDC cytotoxicity to target destructing cancer cells in vitro and exhibit in vivo antitumor activity in mouse xenograft models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a variety of other cargos, such as small molecule antigen (e.g. 2,4-dinitrophenyl (DNP)), can be associated with N terminus of pHLIPs and specifically targeted to the surfaces of cancer cells to induce biological responses, since tumors are putatively acidic ( 27 ). In this study, we engage the extracellular region of murine PD-L1 with the N terminus of pHLIPs and evaluate the function of this fusion protein (PD-L1-pHLIP) to suppress lymphocyte expansion and cytokine production in acidic buffer, providing a potentially innovative avenue to treat inflammatory autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This insertion topology can therefore be used to graft a variety of molecules onto cancer cell surfaces as long as they are conjugated to the N-terminus of pHLIP. [22,38,39] Here, we show that remodeling the surface of cancer cells with a FPR ligand using a pHLIPbased targeting strategy could selectively engage an immune response towards tumors by activating FPR1 on recruited immune cells (Figure 1).…”
Section: Introductionmentioning
confidence: 83%
“…This insertion topology can therefore be used to graft a variety of molecules onto cancer cell surfaces as long as they are conjugated to the N-terminus of pHLIP. [22,38,39]…”
Section: Introductionmentioning
confidence: 99%